(untitled) (Eurasian Journal of Ecology, 2016)
Кіші Алматы өзенінің су сапасын бағалауда түрлі биотикалык индекстердің қолданылу мүмкіндігі зерттелді. Ұлыбританиядағы RIVPACS су сапасын бағалау ұлттық жүйесі аясында жетілдірілген, Average Score Per Taxon Index (ASTP) əдісі- ең жарамды индекс болып танылды. The application of different biotic indices for the water quality’s assessment on the sample of River Kishi-Almaty was considered. Average Score Per Taxon Index (ASTP) which was developed in Great Britain within River Inverterbrate Prediction & Classification System (RIVPACS), it was rewarded as the most sensitive index. Исследована возможность применения различных биотических индексов для оценки качества вод реки Киши Алматы. Наиболее чувствительным индексом признан Average Score Per Taxon Index (ASTP), разработанный в Великобритании в рамках национальной системы оценки качества воды RIVPACS.